A new capitalist order : privatization & ideology in Russia & Eastern Europe - Appel, Hilary (Series in Russian and East European studies., 2004)
"A New Capitalist Order breaks with mainstream empirical studies of privatization in the Soviet Union and Eastern Europe, arguing that privatization was designed and implemented by pro-market reformers not only to distribute gains and losses to powerful supporters, but also to advance a decidedly Western, liberal vision of the new postcommunist state. Moreover, specific ideologies - such as anticommunism, liberalism, or nationalism - profoundly influenced the legitimacy, the power, and even the material preferences of key economic actors and groups within the privatization process."--Jacket.